Criminal statistical indices of environment impairing crimes and social geographic analysis of the perpetrators (Academic Journal of Internal Affairs, 2020)
In the essay I use data of criminal statistics, maps of criminal infection in order to discover temporal and areal features of committing environment impairing. Comparing the known perpetrators of environment and the Hungarian counties I try to highlight those geographical and social facts which could directly influence the occurrence of these types of crimes and the ones which could increase the abuse of criminal opportunities. There are statistics about the registered crimes of environmental impairing between 2005 and 2018 in Hungary. With the help of these data, I got the answer about the Hungarian counties being the most infected areas from criminal point of view and the answer for the fact which environmental impairing types are the most common ones. The social geographical analysis of known perpetrators shows, that also in case of environment impairing are unemployment and non-education significant negative social geographical facts.
Keywords: geography of crimes; environment impairing; social geography